Factors Associated With the Behavior of Implementing Health Protocols Among Students at SMP Negeri 29 North Samarinda - Ruminem, Ruminem; Sari, Rita Puspa; Nopriyanto, Dwi; Widiastuti, Ida Ayu Kade Sri; Muda, Iskandar (Fakultas Kedokteran, 2024)
Background: The Coronavirus Disease 2019 (COVID-19) pandemic in Indonesia has not ended yet. Efforts to accelerate the prevention of Covid-19 transmission in Indonesia apart from accelerating vaccination efforts are also public discipline in implementing health protocols, to break the chain of transmission of COVID-19. Obtained the presence was non-compliance with the behavior of the community, including adolescents, in implementing health protocols for the prevention of Covid-19, this could increase the risk of transmission of Covid-19. Objectives: Research to analyze Factors Associated with the Behavior of Implementing Health Protocols among Students at SMP Negeri 29 North Samarinda. Methods: Research using a cross-sectional design. The population is students of SMPN 29 North Samarinda, the sampling technique uses stratified random sampling and a sample of 189 students. The research instrument was a questionnaire. and data analysis using Chi-square test. Result: The results showed that the behavior of students in implementing the health program was good (50.8%) and bad behavior (49.2%). Factors that were significantly related to student health program implementation behavior were gender (Pvalue=0.016), Knowledge (Pvalue=0.000) and family support (Pvalue=0.001). Meanwhile, the variables of age, information acquisition and vaccination status are not related to the behavior of implementing the Prokes in SMPN 29 students. Conclusion: In conclusion, the factors of gender, knowledge and family support are related to student behavior in implementing health programs. It is recommended that schools still need to provide education on the implementation of the health protocol for adolescents during the Covid-19 pandemic that has not yet been declared over.